Urząd dyrektora muzeum diecezjalnego w aspekcie kanonicznym - Adamczyk, Jerzy (Archiwa, Biblioteki i Muzea Kościelne, 2017)
The following article is devoted to the office of the diocesan museum director in the canonic view. In the first part, the necessity of the diocesan museum director’s job is presented. The second part depicts the qualifications and the formation of the diocesan museum director. The final part is devoted to the duties of the diocesan museum’s leader.